High School Mathematics Teachers’ Digital Competencies in the Costa Rican North Caribbean Region - Jiménez Castro, Maynor (2024)
This article analyzes how the Regional Mathematics Teaching Encounters (EREM in Spanish), organized by various educational institutions in Costa Rica, have influenced the digital skills of secondary school teachers who participated in the events between 2011 and 2021. The focus was on the most active participants in these meetings, using the European Framework for the Digital Competence of Educators (DigCompEdu). The findings show significant levels of digital competence, with scores of B1 in Professional Engagement and Teaching and Learning, and B2 in Digital Content. However, an initial level was observed in the competence of Evaluation and Feedback using digital tools. Finally, the importance of creating spaces for teacher training in the use of classroom technologies to strengthen the digital competencies of mathematics teachers in the region is recognized.